A new species of barb Puntius nigripinnis (Teleostei: Cyprinidae) from southern Western Ghats, India - J.D Marcus Knight; K Rema Devi; T.J Indra; M Arunachalam (Journal of Threatened Taxa, 2012)
Puntius ticto, a widely distributed barb, was long believed to have many variants. Recent research has shown that what was earlier known as P. ticto in different regions of India comprised of many similar looking species such as P. manipurensis, P. muvattupuzhaensis, P. pookodensis, among others. As yet another addition to this complex, we describe Puntius nigripinnis sp. nov. from the Nilgiris and Wyanad area of the southern Western Ghats. Puntius nigripinnis, sp. nov., is distinguished from all other congeners by lacking barbels and having the last unbranched dorsal ray serrated; 20-21 lateral line scales; lateral line incomplete, piercing 3-5 scales; dorsal, anal, pelvic and pectoral fins black in adult males; body pattern consisting of a humeral mark on the 3rd or 4th lateral-line scale and a second larger, band-like spot on the 18th and 19th scale, forming a ring around the caudal peduncle, and only two scales between the second spot and the root of the caudal fin.